Serum sodium abnormality profile in hospitalized elderly patients in a tertiary care centre from north India: a cross sectional observational study - Kumar, Soni; Guleria, Trilok C.; Nand, Laxmi; Gupta, Dalip; Thakur, Manish (International Journal of Research in Medical Sciences, 2017)
Background: Serum sodium disorder is most common electrolyte disorder in hospitalized patients. It is associated with significant morbidity and mortality. In developing countries like India; there is continuous increase in elderly population due to improving health care. There is lack of sufficient Indian data on clinical profile, causes, and outcome in elderly hospitalized patients with sodium disorder. We studied incidence, etiology, clinical profile, and outcome of sodium disorders after the treatment during the hospital stay in elderly patients at our institution so that guidelines could be formulated to manage the patients. Methods: 100 consecutive patients of serum sodium abnormality coming to indoor wards of medicine department over a period of one year were enrolled. Detailed history was taken, clinical presentation reviewed and examination were carried out. All patients were followed closely during hospital stay and necessary investigations were done to establish the cause. Results: The mean age of patients in the study was 71.26 ±7.8 years (range 60-96 years). Maximum numbers of patients were in the age group of 61-65 years (31%). Out of 100 patients, 54% were males and 46% were females. Out of 100, 48% patients had HTN,38% had DM, 19% had CKD. Abnormal behavior, nausea, vomiting were the predominant symptoms. CKD and drugs intake were the chief causes of the serum sodium abnormality due to abnormal fluid and water homeostasis. The mortality rate was significantly higher in Hypernatremia patients i.e.62 % as compared to hyponatremia patients 26% which was related to severity of serum sodium abnormality, rapid onset, long hospital stays and severity of underling illness. Conclusions: In our study CKD, drugs chiefly thiazide like diuretics were the most common causes of hyponatremia and dehydration was most common cause for hypernatrmia. Serum sodium disorders were associated with high mortality and morbidity in elderly hospitalized patients.